Development of nucleus-targeted histone-tail-based photoaffinity probes to profile the epigenetic interactome in native cells - Yu Wang; Jian Fan; Xianbin Meng; Qingyao Shu; Yincui Wu; Guo-Chao Chu; Rong Ji; Yinshan Ye; Xiangwei Wu; Jing Shi; Haiteng Deng; Lei Liu; et al. (Nature Communications)
Abstract Dissection of the physiological interactomes of histone post-translational modifications (hPTMs) is crucial for understanding epigenetic regulatory pathways. Peptide- or protein-based histone photoaffinity tools expanded the ability to probe the epigenetic interactome, but in situ profiling in native cells remains challenging. Here, we develop a nucleus-targeting histone-tail-based photoaffinity probe capable of profiling the hPTM-mediated interactomes in native cells, by integrating cell-permeable and nuclear localization peptide modules into an hPTM peptide equipped with a photoreactive moiety. These types of probes, such as histone H3 lysine 4 trimethylation and histone H3 Lysine 9 crotonylation probes, enable the probing of epigenetic interactomes both in HeLa cell and hard-to-transfect RAW264.7 cells, resulting in the discovery of distinct interactors in different cell lines. The utility of this probe is further exemplified by characterizing interactome of emerging hPTM, such as AF9 was detected as a binder of histone H3 Lysine 9 lactylation, thus expanding the toolbox for profiling of hPTM-mediated PPIs in live cells.